2012
DOI: 10.3844/ajbbsp.2012.99.104
|View full text |Cite
|
Sign up to set email alerts
|

Papain, a Plant Enzyme of Biological Importance: A Review

Abstract: Papain is a plant proteolytic enzyme for the cysteine proteinase family cysteine protease enzyme in which enormous progress has been made to understand its functions. Papain is found naturally in papaya (Carica papaya L.) manufactured from the latex of raw papaya fruits. The enzyme is able to break down organic molecules made of amino acids, known as polypeptides and thus plays a crucial role in diverse biological processes in physiological and pathological states, drug designs, industrial uses such as meat te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Papain occurs in all parts of the tree except the root [40]. A well managed papaya production has re-corded higher papain yield of 8.17 g·fruit −1 and highest papain of 686.29 g·plant −1 in a period of 6 mo [35]. As to the analysis of the protease activity, results showed that papain at pH 5.5 had a protease activity of 2655 units·g −1 and 285 units·g −1 only at pH 9.0 ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Papain occurs in all parts of the tree except the root [40]. A well managed papaya production has re-corded higher papain yield of 8.17 g·fruit −1 and highest papain of 686.29 g·plant −1 in a period of 6 mo [35]. As to the analysis of the protease activity, results showed that papain at pH 5.5 had a protease activity of 2655 units·g −1 and 285 units·g −1 only at pH 9.0 ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine protease enzyme is found naturally in papaya (C. papaya L.) manufactured from the latex of raw papaya fruits. The enzyme is able to break down organic molecules made of amino acids, known as polypeptides and thus plays a crucial role in diverse biological processes in physiological and pathological states, drug designs and industrial uses [35] and the enzyme is the most thoroughly characterized of the thiol proteinases [36]. Papain has revealed to be an enzymatic protein of significant biological and economic importance, since the unique structure of papain provides functionality and helps explain how this proteolytic enzyme works and makes it valuable for a variety of purposes [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It requires a free sulfhydryl group for its catalytic activity. The papain, a photolytic enzyme isolated from papaya latex is capable to break down polypeptides which are organic molecule consist of amino acids (Amri and Mamboya, 2012).…”
Section: Introductionmentioning
confidence: 99%